Measurements of the diffuse Galactic synchrotron spectral index and curvature from MeerKLASS pilot data. Issue 4 (23rd November 2021) - Irfan, Melis O; Bull, Philip; Santos, Mario G; Wang, Jingying; Grainge, Keith; Li, Yichao; Carucci, Isabella P; Spinelli, Marta; Cunnington, Steven
ABSTRACT: 21 cm intensity mapping experiments are bringing an influx of high spectral resolution observational data in the ∼100 MHz–1 GHz regime. We use pilot 971–1075 MHz data from MeerKAT in single-dish mode, recently used to test the calibration and data reduction scheme of the upcoming MeerKLASS survey, to probe the spectral index of diffuse synchrotron emission below 1 GHz within 145° < α < 180°, −1° < δ < 8°. Through comparisons with data from the OVRO Long Wavelength Array and the Maipu and MU surveys, we find an average spectral index of −2.75 < β < −2.71 between 45 and 1055 MHz. By fitting for spectral curvature with a spectral index of the form β + c ln(ν / 73 MHz), we measure β = −2.55 ± 0.13 and c = −0.12 ± 0.05 within our target field. Our results are in good agreement (within 1σ) with existing measurements from experiments such as ARCADE2 and EDGES. These results show the calibration accuracy of current data and demonstrate that MeerKLASS will also be capable of achieving a secondary science goal of probing the interstellar medium.